The use of technology in Portuguese higher education: Building bridges between teachers and students - Mesquita, Anabela (2018)
The development of technologies together with the new formats, pedagogies and methodologies that they make possible and the characteristics of the youngsters are forcing higher education institutions to change. In order to fill the gap between school and the world outside school, some teachers are adopting and using these technologies. However, there is not enough information available about how they are doing that, if they really use them and, when they do, how do they do it. In this quantitative study, teachers and students were questioned about the use of technologies in the classroom. Results show that although teachers know how to use technology, and advocate they use it, it is still not clear the purpose they use it. The reasons advanced for this situation are the technology itself and, in some cases, with the curriculum. Future work should focus on the analysis of the way teachers really use the technology, thus it will be possible to provide the training and support to help them to fully take advantage of the technologies with pedagogical purposes.